2003
DOI: 10.2337/diabetes.52.3.688
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles of Nondiabetic and Diabetic Obese Mice Suggest a Role of Hepatic Lipogenic Capacity in Diabetes Susceptibility

Abstract: Obesity is a strong risk factor for the development of type 2 diabetes. We have previously reported that in adipose tissue of obese (ob/ob) mice, the expression of adipogenic genes is decreased. When made genetically obese, the BTBR mouse strain is diabetes susceptible and the C57BL/6J (B6) strain is diabetes resistant. We used DNA microarrays and RT-PCR to compare the gene expression in BTBR-ob/ob versus B6-ob/ob mice in adipose tissue, liver, skeletal muscle, and pancreatic islets. Our results show: 1) there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 42 publications
8
111
0
2
Order By: Relevance
“…For example, up-regulation of Rad (a Ras-oncogene associated with diabetes), heat shock 70kD protein, and receptors for PDGF and endothelin, and down-regulation of general transcription and translation factors, and of cadherin and MHC have been observed in the skeletal muscle of insulin-resistant Pima Indians [7] and in Type 2 diabetic patients [8]. In addition, up-regulation of epidermal growth factor receptor and down-regulation of fatty acid-associated enzymes, fibronectin, VCAM1, MHC, plasminogen, SOD2, FMO5 and complement C3 have been observed in the liver of ob/ob mice [10,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, up-regulation of Rad (a Ras-oncogene associated with diabetes), heat shock 70kD protein, and receptors for PDGF and endothelin, and down-regulation of general transcription and translation factors, and of cadherin and MHC have been observed in the skeletal muscle of insulin-resistant Pima Indians [7] and in Type 2 diabetic patients [8]. In addition, up-regulation of epidermal growth factor receptor and down-regulation of fatty acid-associated enzymes, fibronectin, VCAM1, MHC, plasminogen, SOD2, FMO5 and complement C3 have been observed in the liver of ob/ob mice [10,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, microarray profiling of skeletal muscle tissue of Type 2 diabetic patients [7,8] and of healthy humans treated with insulin [9] has been reported. Although the liver is central for glucose homeostasis, microarray profiling of diabetic liver has been done only in Ob/Ob mice, a genetically obese rodent model of diabetes [10,11,12]. We have now used it to clarify the transcriptional alterations in the liver that are associated with the pathophysiology of Type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Benefits of enhanced triglyceride storage on insulin sensitivity have also been demonstrated in myocytes (38). Similarly, it has been suggested that differences in hepatic lipogenesis underlie the resistance of C57Bl/6J-ob/ob mice to diabetes by comparison with BTBR-ob/ob mice (39). Future studies will be required to define changes in hepatic flux of lipid metabolites induced by a CDD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Txnip deficiency was also able to rescue severely obese and insulin-resistant BTBRob/ob mice lacking leptin from diabetes, as demonstrated by our double-mutant congenic BTBRlep ob/ob txnip hcb/hcb (BTBR.ob/hcb) mice (9). BTBRob/ob mice are considered one of the most stringent models of type 2 diabetes, since, unlike B6ob/ob BTBRob/ob mice typically develop severe diabetes already at 6 weeks of age and completely decompensate at around 10 weeks (10). In contrast, Txnip-deficient BTBR.ob/ hcb mice remained normoglycemic for over 6 months.…”
mentioning
confidence: 99%